The Influence of Principal’s Role, and School Culture on Elementary School Teachers’ Competence - Andi Yusuf, Mohammad; Rasiman, Rasiman; Sumarno, Sumarno (Jayapangus Press, 2025)
This study focuses on the problem of low teacher competence in elementary schools in Petarukan District, Pemalang Regency, where only 46% of 80 schools demonstrate good learning quality. The research aims to analyze the influence of the principal’s role and school culture on teacher competence. Using a quantitative correlational ex post facto design, data were collected from 242 elementary school teachers through Likert-scale questionnaires assessing the principal’s role (managerial, entrepreneurial, and supervisory dimensions), school culture, and teacher competence (pedagogical, personality, social, and professional aspects). Descriptive statistics show the principal’s role is rated fairly well (mean=129.46; ideal midpoint=87), with entrepreneurial development as the strongest dimension and supervision the weakest. Teacher competence also falls within a fairly good category (mean=151.85; ideal midpoint=105), with personality as the strongest and professional competence as the weakest dimension. Pearson’s correlation coefficient (r=0.588; p<0.05) indicates a strong relationship between the principal’s role and teacher competence. Simple linear regression reveals that a 1% improvement in the principal’s role increases teacher competence by 0.598%, explaining 34.6% of variance. Theoretically, these findings reinforce the importance of effective school leadership and positive school culture in fostering teacher competence. Practically, the results recommend strengthening principals’ supervisory functions and entrepreneurial program development, as well as capacity building for principals, to optimize educational quality improvement.